Less is More? The child quantity-quality trade-off in early 20th century England and Wales - Alan Fernihough (Queen's University Centre for Economic History (QUCEH), 2017)
Whilst the child quantity-quality (QQ) model is theoretically well-established, the empirical literature offers only partial support. Motivated by the limited causal empirical evidence in both historic and contemporary societies, this study examines the relationship connecting fertility and child quality for individual families in England and Wales at the start of the 20th century. Using data from the 1911 census returns, I estimate whether reductions in family size reduce the probability of leaving school. To account for the endogenous nature of fertility decisions, I use the sex composition of the first two births in families with at least two children as an instrumental variable (IV) for family size. Overall, I find evidence in support of a child QQ effect, as children in the 13-15 age cohort born into smaller families were more likely remain in school. Whilst the IV results are very similar to the non-IV ones, one drawback is that the IV estimates are quite imprecise.
Keywords: J10; N3; O10; 330; Quantity-Quality; Human Capital; Demographic Transition